Building blocks of Chef's competency and articles distribution: a literature review - Hussein, Haslina (Human Resource Management Academic Research Society, 2023)
Research on chefs is underrepresented in the hospitality literature. This article examined the expertise of chefs by identifying the journals, temporal scope, and the distribution of countries of origin. By searching databases such as Google Scholar, Science Direct, Emerald, and Scopus, 37 relevant articles from 23 journals were examined. This study also identifies the competency components needed in a chef's career and suggestions for future research. The findings indicate that a cook's competencies can be broken down into three categories, namely functional, core, and general competencies. These categories are shown below, along with examples of specific skills that build up a chef's competency blocks. It has been discovered that the qualities a chef needs include organisational competencies, self-management competencies, and innovative culinary competencies.